A Useful Device to Measure Kinetics of Platelet Contraction - George, Mitchell J. (ASAIO J, 2018)
Platelet contraction provides a minimally invasive source for physiological information. In this paper we describe a device that directly measures the kinetics of platelet contraction. Whole blood is injected between acrylic plates and an adherent clot forms. The bottom plate is fixed, and the top plate is attached to a wire cantilever. Platelet contraction drives deflection of the wire cantilever which is captured by a camera. Force generated by the clot with time is derived using beam equations. Force derivations were verified using a microelectromechanical (MEMS) force sensor. Kinetics of clot contraction were defined, including maximum contraction force (F(MAX)), lift-off time (T(LIFTOFF)), and contraction rate (CR). Metrics were compared to optical aggregometry and thromboelastography. F(MAX) correlates with optical aggregometry maximal amplitude with a Spearman’s rho of 0.7904 and p = 0.0195 and thromboelastography maximal amplitude with a Spearman’s rho of 0.8857 and p = 0.0188. T(LIFTOFF) correlates with optical aggregometry lag time with a Spearman’s rho of 0.9048 and p = 0.002. This preliminary study demonstrates the repeatability of a useful platelet contraction device and its correlation with thromboelastography and optical aggregometry, the gold standard platelet function test.